2002
DOI: 10.1080/00377310209517659
|View full text |Cite
|
Sign up to set email alerts
|

Practice innovations in mental health services to children and families: New directions for Massachusetts∗

Abstract: This research report highlights selected findings that describe the characteristics of excellent, innovative programs for high-risk children and adolescents in Massachusetts. The conclusions reported are based on interviews with administrators and providers at nine sites. A research consortium composed of policy makers, administrators, clinicians, and academic researchers recommended the site selections. The study describes a spectrum of innovative practices used to help youngsters in severe crises. Innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our study (Lightburn et al, 2002), we came to the following conclusion about therapeutic interventions in these programs:…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…In our study (Lightburn et al, 2002), we came to the following conclusion about therapeutic interventions in these programs:…”
mentioning
confidence: 83%
“…Lightburn et al (2002) describe clinical dilemmas found in wraparound processes. These include an inability to engage and sustain relationships with families who are extremely isolated; sustain ongoing collaborative relationships with multiple service providers; clarify the nature of therapeutic conversations; provide resources and support independence in families; and terminate families from intensive services.…”
Section: Wraparound Processes: Principles and Dilemmasmentioning
confidence: 99%
See 1 more Smart Citation